Effect of newer antioxidants on the bond strength of composite on bleached enamel - M Manoharan; K K Shashibhushan; P Poornima; Sathyajith N Naik; Disha Patil; A S Shruthi (Wolters Kluwer Medknow Publications, 2016)
Aim: The study aims to evaluate the effect of the application of two antioxidants on the bond strength of composite resin to bleached enamel. Materials and Methods: Eighty enamel surfaces were obtained from forty human extracted premolars. Specimens were randomly divided into four groups (n = 20). Group 1: No bleaching (control); Group 2a: Bleaching with 15% carbamide peroxide gel; Group 2b: Bleaching, followed by application of 10% sodium ascorbate gel; Group 2c: Bleaching, followed by application of 5% proanthocyanidin agent. Surfaces were etched followed by application of total etch bonding system, and composite resin cylinders were bonded. Specimens were tested for shear bond strength. Statistical Analysis Used: One-way analysis of variance was used for multiple group comparison and post hoc Tukey's test for individual group-wise comparison. Results: Significantly higher shear bond strength values were observed in Group 2c and 2b as compared with Group 1 and 2a (P < 0.05). Among the antioxidants, Group 2c showed significantly higher shear bond strength values than Group 2b (P < 0.05). Conclusion: It can be concluded that the use of antioxidant before bonding procedures on bleached enamel completely neutralizes the deleterious effects of bleaching and increases the bond strength significantly.